2005
DOI: 10.1007/s10620-005-2868-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digestion of Collagen and Elastin on Histomorphometry and the Zero-Stress State in Rat Esophagus

Abstract: To understand the physiology and pathology of the esophagus, it is necessary to know the mechanical properties and their dependence on the structural components. The aim of this study was to investigate the effect of collagenase and elastase on the morphological and biomechanical properties in the no-load and zero-stress states in the rat esophagus. Twenty tissue rings from each esophagus of seven normal rats were sectioned in an organ bath containing calcium-free Krebs solution with dextran and EGTA. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
5
16
0
Order By: Relevance
“…Greenwald et al (1997) showed in blood vessels that the true stress-free state can only be reached by partial destruction of the vessel wall. This is in line with our previous study showing that enzymatic digestion of elastin or collagen changes the opening angle and residual strain distribution in the rat oesophageal wall (Fan et al, 2005). Hence, the opening angle and residual strain distribution are associated with non-homogeneity in the structure and/or composition of the oesophageal wall.…”
Section: A Three-layer Modelsupporting
confidence: 92%
“…Greenwald et al (1997) showed in blood vessels that the true stress-free state can only be reached by partial destruction of the vessel wall. This is in line with our previous study showing that enzymatic digestion of elastin or collagen changes the opening angle and residual strain distribution in the rat oesophageal wall (Fan et al, 2005). Hence, the opening angle and residual strain distribution are associated with non-homogeneity in the structure and/or composition of the oesophageal wall.…”
Section: A Three-layer Modelsupporting
confidence: 92%
“…The PEC is anatomically located in the connective tissue because the contractile element of the smooth muscle has been shown not to contribute significantly to passive tension [33]. It is more likely that the shape of the passive stress-strain curves depends on connective tissue morphology and structural components such as collagen [7,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous zero-stress state analysis has been based on data from rat, rabbit and guinea pig [1,5,6,9,10,15] . In yet unpublished studies, the zero-stress morphology data were obtained from five male 300 g Wistar rats.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The tests were conducted in a tensile test machine consisting of an organ bath, motion table, force transducer and electronics [15,16] . The force and displacement curves were obtained simultaneously during the tensile test.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation